CELL-ZONAL TEXTURES OF TINGUAITES FROM THE KOLA PENINSULA - Voitsekhovsky Y.L.; Shpachenko A.K.; Skiba V.I. (My University, 1997)
Textures of tinguaite dykes cutting the alkaline Khibiny massif in the Kola Peninsula, Russia, are described. They are characterized by a combination of a fractal microfracture network dividing rock into pencil-like cells and of a concentric rhythmical zonation in almost all of them. The latter is formed by interchange of volatile-enriched and volatile-depleted mineral zones. The location of the textures only where dykes contact host khibinites appears to point out the contraction nature of the microfracture network. The cooling time calculated agrees well with this hypothesis. The zonation appears to have arisen through autometamorphic processes with two main competing factors, namely (a) overall cooling of the system and (b) periodic depletion of it in some elements, mainly Na and K. Another mechanism which may be applied to explain the zonation is the known Marangoni Instability effect at the early stage of evolution of the volatile-saturated phonolite melt. Thus, tinguaite textures are caused by nonspecific influences external to the system and may be regarded as an example of self-organization in nature.